Territorialidades das igrejas evangélicas nas comunidades tradicionais da Amazônia Central - José Diego Gobbo Alves; Heloísa Corrêa Pereira; Álvaro de Oliveira D’Antona (Confins)
In the Central Amazon, popular movements associated with the Catholic religion were crucial for the socio-spatial formation of traditional communities in the model we know today. However, as observed in Brazil, the number of evangelical Christians has increased significantly in recent years, a growth associated with the territorial expansion of evangelical religious temples. In this article, we analyze the territorialities of evangelical churches and their centrality in traditional communities of the Amazon, with a case study focusing on the Mosaic of Protected Areas of the Lower Negro River (MBRN), located in the states of Amazonas and Roraima. The methodology involved fieldwork conducted in 2022 in the region, including participant observation and the administration of questionnaires to the leaders of 119 visited communities and 327 household surveyed. The findings indicate that evangelical churches currently play a key role in the socio-spatial organization of communities, a role once exercised by the Catholic Church. This involves territorial strategies such as the construction of religious temples, spatial mobility of pastors and congregants between communities, and the presence of pastors in the daily lives of communities as community leaders. These territorialities configure networked territories that connect communities in a spatial organization beyond the local level.